How long and how much? Wait times and costs for initial private child mental health appointments. (10th November 2020) - Mulraney, Melissa; Lee, Cindy; Freed, Gary; Sawyer, Michael; Coghill, David; Sciberras, Emma; Efron, Daryl; Hiscock, Harriet
Abstract : Aim: To determine: (i) wait times and out‐of‐pocket costs for children attending private specialists for initial mental health appointments; and (ii) whether these differed between specialists working in metropolitan versus rural areas and in low, medium and high socio‐economic areas. Methods: Prospective secret shopper study whereby a researcher posed as a parent seeking an appointment for her child with anxiety or attention‐deficit/hyperactivity disorder. We contacted 317 private paediatrician, psychiatrist and psychologist practices in Victoria and South Australia between 12 March and 5 May 2019. Results: One third (29.8%) of private practices were closed to new referrals. The average wait times for paediatricians, psychiatrists, and psychologists were 44, 41 and 34 days, respectively. Average out‐of‐pocket costs quoted were AU$120 for paediatricians, AU$176 for psychiatrists and AU$85 for psychologists. Conclusion: Parents face extensive wait times and substantial out‐of‐pocket costs when seeking private mental health services for their child.